Long-term Behavioral Consequences of the COVID-19 Pandemic for Autistic Individuals and Their Mothers - Genc, Herdem Aslan; Doenyas, Ceymi; Aksu, Yasemin; Musaoglu, Mirac Nur; Uzunay, Sena; Mutluer, Tuba (SPRINGER/PLENUM PUBLISHERS, 2024)
Long-term effects of the COVID-19 pandemic on autistic individuals and their families are recently emerging. This study investigated these effects in 40 mother-child dyads by measuring the behavioral problems of autistic individuals (via Aberrant Behavior Checklist) and their mothers' anxiety levels (via Beck Anxiety Inventory) during the pre-pandemic period, one month after, and one year after its onset. One year into the pandemic, aberrant behaviors of autistic individuals worsened only for those whose mothers had high anxiety levels. The continued negative impact of the COVID-19 pandemic on the behavior of autistic individuals is related to their mother's anxiety level, highlighting the need to support maternal mental health in families with individuals with autism.
Keywords: Anxiety; Autism spectrum disorder; Behavior; COVID-19; Mother-child dyad; SPECTRUM DISORDER; CHILDREN; PARENTS; IMPACT; ASSOCIATION; CHECKLIST; Psychology